2011
DOI: 10.4103/0974-9233.84055
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes of conductive keratoplasty to treat hyperopia and astigmatism after laser in situ keratomileusis and photorefractive keratectomy

Abstract: Aim:To determine the effect of conductive keratoplasty (CK) for the treatment of induced hyperopia and astigmatism after complicated myopic laser in situ keratomileusis (LASIK) or photorefractive keratectomy (PRK).Materials and Methods:In this interventional case series, 11 eyes of seven subjects with a history of previous LASIK or PRK with inadequate stromal bed or flaps complications were enrolled. Inclusion criteria included residual spherical hyperopia of 1.00 to 3.00 diopters (D) and cylinder of –0.75 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“… 176 However, it seems that CK alone may not be effective for high astigmatism and keratoconus, and it needs to be combined with other options, or the surgeon may need to apply more spots in flat areas. 174 , 177 Using topography-guided conductive keraoplasty (TGCK) in advanced keratoconus, Kato et al observed stable vision improvement at 12 months after surgery in 70% of the eyes. 178 This surgical technique is suggested for cases of non-progressive advanced keratoconus who cannot tolerate contact lenses.…”
Section: Methodsmentioning
confidence: 99%
“… 176 However, it seems that CK alone may not be effective for high astigmatism and keratoconus, and it needs to be combined with other options, or the surgeon may need to apply more spots in flat areas. 174 , 177 Using topography-guided conductive keraoplasty (TGCK) in advanced keratoconus, Kato et al observed stable vision improvement at 12 months after surgery in 70% of the eyes. 178 This surgical technique is suggested for cases of non-progressive advanced keratoconus who cannot tolerate contact lenses.…”
Section: Methodsmentioning
confidence: 99%